1995
DOI: 10.1210/jcem.80.8.7629255
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous catecholamines suppress thyrotropin secretion during the early follicular phase of the menstrual cycle.

Abstract: The physiological role of hypothalamic catecholamines in the regulation of TSH secretion in humans has not been studied extensively. We administered the catecholamine synthesis inhibitor alpha-methyl-p-tyrosine (AMPT) to five women in the early follicular phase (one of menstrual cycle days 2-5) of the menstrual cycle and compared TSH secretion patterns to those in five women at the same time in the cycle who did not receive AMPT. From 0800-1600 h, volunteers had an i.v. line placed, through which blood was wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In agreement with previous studies applying the AMPT paradigm in healthy volunteers [ 17 , 29 , 34 , 35 ], AMPT administration increased serum PRL levels significantly shortly after its first administration, and PRL levels fell thereafter, even though more AMPT was administered. AMPT-induced DA depletion consistently produced a two- to ninefold increase in PRL levels [ 17 , 29 , 34 , 35 ]. Previously, PRL has been used as a marker of the effectiveness of AMPT as an inhibitor of endogenous DA synthesis [ 35 ] because hypothalamic DA is known to inhibit PRL release at the level of the pituitary gland [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies applying the AMPT paradigm in healthy volunteers [ 17 , 29 , 34 , 35 ], AMPT administration increased serum PRL levels significantly shortly after its first administration, and PRL levels fell thereafter, even though more AMPT was administered. AMPT-induced DA depletion consistently produced a two- to ninefold increase in PRL levels [ 17 , 29 , 34 , 35 ]. Previously, PRL has been used as a marker of the effectiveness of AMPT as an inhibitor of endogenous DA synthesis [ 35 ] because hypothalamic DA is known to inhibit PRL release at the level of the pituitary gland [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…AMPT-induced DA depletion consistently produced a two- to ninefold increase in PRL levels [ 17 , 29 , 34 , 35 ]. Previously, PRL has been used as a marker of the effectiveness of AMPT as an inhibitor of endogenous DA synthesis [ 35 ] because hypothalamic DA is known to inhibit PRL release at the level of the pituitary gland [ 36 ]. However, DA is not the only factor controlling PRL levels, and there is no direct relation between hypophysial stalk DA levels and serum PRL levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the use of AMPT as a pharmacological clamp of catecholamine activity was confirmed by others (Plosker et al, 1995). Based on these observations it can be concluded that AMPT can induce consistently a biologically significant decrease in catecholamine production and release.…”
Section: Discussionmentioning
confidence: 66%
“…Added in physiolog c blind crossover design in which active and control tests were gic concentrations, exogenous 6-MS was recovered at 81-86%. separated by [4][5][6] weeks. Both tests were performed in women Thentra-ass CVgwas3-8.6% depenineo t concen-…”
mentioning
confidence: 99%
“…No crystal formation those of the Diagnostic and Statistic Manual of Mental Disorders, was detected in the urine of any of the subjects studied. by[4][5][6] weeks. Both tests were performed in women Thentra-ass CVgwas3-8.6% depenineo t concen-The intra-assay CV weas 3.3-8.6% depending oi1 the concenduring the early follicular phase of the menstrual cycle (cycle tration, and the interassay CV was 4.9%.…”
mentioning
confidence: 99%